Accelerated gastric emptying is associated with improved aspiration efficiency in obesity - Vargas, Eric J (BMJ Open Gastroenterol, 2019)
BACKGROUND: The overall effectiveness of aspiration therapy (AT) for obesity relies on optimal aspiration timing after a meal, which can vary depending on a patient’s rate of gastric emptying (GE). Our aim was to identify if baseline GE rates were associated with differences in aspiration efficiency (AE). METHODS: Subjects from an ongoing AT clinical trial were enrolled in this study. AE was calculated as the absolute gastric residual and calories aspirated at 20 and 40 min. Participants were then divided by baseline GE rate into two groups (slow vs fast). Wilcoxon rank-sum test was used to compare AE at 20 and 40 min between the groups. Exploratory linear regression was used to assess relationship between GE and AE. RESULTS: 7 patients (85% female) were coenrolled in the study. Mean age and body mass index were 39.8±9.44 and 43±5, respectively. AE did not significantly differ between the 20 and 40 min time points for the group as a whole (34.3% vs 36.9%; p>0.5). However, those with fast GE aspirated more calories than those with slow GE (20 min: 200 kcal vs 72.5 kcal; 40 min: 154 kcal vs 63 kcal) (p=0.05). On linear regression, delayed GE was associated with poorer aspiration (20 min: β=−107 calories; p=0.019; R(2)=0.7). 4/7 patients had significant differences in residual/caloric aspiration across the two time points. CONCLUSION: Patients undergoing AT may benefit from a GE test to optimise their AE. Paradoxically faster GE times saw better aspiration. Prospective studies are revealing a personalised approach to obesity.